Rebenko M. Y. Pragmatic translation deformation peculiarities at the text modality category level in Ukrainian and Russian target texts - Rebenko M. Y. (Philological Treatises, 2020)
Analyzed are peculiarities of pragmatic translation deformation phenomenon at the level of fragmentary pragmatically modal fields and their characteristics in target texts. Substantiated is dependence of translation deformation degree on objective text items and their subjective target equivalents correlation level.